Back Cover: Generation and Structuring of Multipartite Entanglement in a Josephson Parametric System (Adv. Quantum Technol. 1/2023). Issue 1 (10th January 2023) - Petrovnin, Kirill Viktorovich; Perelshtein, Michael Romanovich; Korkalainen, Tero; Vesterinen, Visa; Lilja, Ilari; Paraoanu, Gheorghe Sorin; Hakonen, Pertti Juhani
Abstract : Highly entangled multimode states in continuous variables are a valuable resource in quantum information. The cover illustrates the 4‐partite correlations of microwave modes generated from electromagnetic vacuum via three‐wave mixing process in a Josephson parametric amplifier by using three pumps. As shown in article number 2200031 by Kirill Viktorovich Petrovnin, Pertti Juhani Hakonen, and co‐workers, this results in genuine multipartite entanglement. A fully controllable pump scheme can provide a comprehensive manipulation of the structure of the generated entangled states.